2016
DOI: 10.1111/bcpt.12567
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Interaction of Tramadol with Gabapentin in Experimental Mononeuropathic Pain

Abstract: Neuropathic pain is the result of injury to the nervous system, and different animal models have been established to meet the manifestations of neuropathy. The pharmacotherapy for neuropathic pain includes gabapentin and tramadol, but these are only partially effective when given alone. The aim of this study was to assess the antinociceptive interaction between both drugs using the isobolographic analysis and changes of the IL-1b concentration in a mouse model of neuropathic pain (partial sciatic nerve ligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The present study demonstrated that antinociception induced by gabapentin combined to tramadol was superior to their monotherapy effect. These results are in agreement with multiple animal studies that used various experimental pain models in which dose‐dependent antinociception has been demonstrated with gabapentin or tramadol in different murine pain models, such as tail flick, formalin hind paw, hot plate, acetone test, and von Frey test .…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that antinociception induced by gabapentin combined to tramadol was superior to their monotherapy effect. These results are in agreement with multiple animal studies that used various experimental pain models in which dose‐dependent antinociception has been demonstrated with gabapentin or tramadol in different murine pain models, such as tail flick, formalin hind paw, hot plate, acetone test, and von Frey test .…”
Section: Discussionsupporting
confidence: 91%
“…Thus gabapentin amplifies the analgesic effects of tramadol. 21 The combination of gabapentin and tramadol produces better analgesia than with tramadol alone.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of CoPP, CORM-2, and SnPP combined with pregabalin or gabapentin were selected as those that produced a relevant effect in accordance with other studies and with the dose–response performed in this study. 19 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%